(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examined the impact of error correction strategies on the interest of senior secondary school students in Economics in Udenu Local Government Area, Enugu State. A quasi-experimental design with non-equivalent pretest and posttest control groups was used. The study involved 933 SS2 Economics students, with a sample of 120 students selected through multi-stage sampling from four secondary schools. The Interest Inventory Test (IIT) was developed, validated, and used for data collection, achieving a reliability score of 0.77. Data were analyzed using Mean, Standard Deviation, and Analysis of Covariance (ANCOVA) at a 0.05 significance level. The results indicated that students taught with the students’ correction strategy showed a slightly higher interest in Economics compared to those taught with the teacher correction strategy. A significant difference was found in favor of the students’ correction strategy. Both strategies were effective in enhancing students’ interest in Economics. The study recommended that Economics teachers receive training from the Ministry of Education on using both error correction strategies to boost students’ interest in the subject. The findings suggest that adopting the students’ correction strategy in teaching Economics can significantly promote student interest in the subject.